Legal Protection for Consumers Against the Presence of Hazardous Chemical Substance Sodium Dehydroacetate in Food Products - Dini, Arinda Prima; Caesar Purwanto, Aldira Mara Ditta (fakultas hukum universitas PGRI Semarang, 2025)
This research aims to examine the legal protection and liability provided to consumers against the presence of hazardous chemical substances in food products. This study employs a normative legal research method with a prescriptive approach to formulate recommendations for addressing the identified legal issues. It utilizes both statutory and conceptual approaches. The research findings indicate that legal protection consists of two types: preventive and repressive. Preventive legal protection is carried out by the National Agency of Drug and Food Control (BPOM) as a government institution responsible for food safety supervision. Meanwhile, repressive legal protection grants consumers the right to file claims when they suffer losses, either through litigation or non-litigation mechanisms. Keywords: Legal Protection, Consumers, Sodium Dehydroacetate.